2019
DOI: 10.1080/09546634.2019.1690621
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of colchicine in inflammatory skin diseases: a retrospective, monocentric study in a large tertiary center

Abstract: Introduction: Colchicine is an ancient, but rarely used drug. Little data exist on its efficacy and safety in patients suffering from skin diseases. The objective of our study was to determine whether colchicine showed favorable efficacy and safety in our patients during the last 20 years.Methods: The hospital database was searched for patients treated with colchicine in the last 20 years (January 1, 1998 to December 31, 2017). Overall, total of 41 patients were included in our study.Results: In 63.4% of all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Colchicine is an effective drug for neutrophilic disorders, and we have found it useful in palmoplantar pustulosis, amyloidosis, aphthosis, and vasculitis [Figures 2 - 4 ]. A recent study has used it successfully in aphthosis and leucocytoclastic vasculitis[ 14 ] while other authors have used it for autoinflammatory diseases,[ 15 ] and neutrophilic urticaria. [ 16 ] An overview of the indications is given in the table below [ Table 1 ].…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colchicine is an effective drug for neutrophilic disorders, and we have found it useful in palmoplantar pustulosis, amyloidosis, aphthosis, and vasculitis [Figures 2 - 4 ]. A recent study has used it successfully in aphthosis and leucocytoclastic vasculitis[ 14 ] while other authors have used it for autoinflammatory diseases,[ 15 ] and neutrophilic urticaria. [ 16 ] An overview of the indications is given in the table below [ Table 1 ].…”
Section: Indicationsmentioning
confidence: 99%
“…Colchicine is effective in this disorder. [ 14 31 ] Colchicine in a dose of 0.5 mg twice daily was administered to 13 patients by Callen et al . [ 32 ] Disease was controlled completely in 9 patients and partial control was observed in 3 patients.…”
Section: Indicationsmentioning
confidence: 99%
“…The AEs are mainly gastrointestinal symptoms, such as vomiting, diarrhea, and nausea, and affect up to 10% of patients treated with the labelled dosage. Other AEs include muscular damage and anagen or telogen effluvium, according to the drug dosage [2][3][4]. Other AEs, such as cardiac arrhythmias, cardiac failure, kidney disease, and myelosuppression are related to the overdosage.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest use of colchicine as mitotic inhibitors and for induction of polyploids is reported in 1937 [30,31] and is still popular today in various plant breeding programs [31][32][33]. It is also used for the treatment of Behcet's syndrome [34,35] and Alzheimer disease [36]. It is also reported that crude ethanolic extracts and different fractions showed lower activity (29-61%) against acetylcholinesterase and no activity against urease [37,38].…”
Section: Introductionmentioning
confidence: 99%